2021
DOI: 10.15330/pcss.22.1.110-116
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Cu, Ni, Mn in Boron-Rich Fe-B-C Alloys

Abstract: In the present study, the microstructure development and mechanical properties of the cast boron-rich Fe–B–C alloys cooled at 10 and 103 K/s were investigated as functions of alloying elements additions. These alloys were prepared in the following compositional ranges: B (10–14 wt.%), C (0.1–1.2 wt.%), M (5 wt.%), where M – Cu, Ni or Mn, balance Fe. Structural properties were characterized by quantitative metallography, X-Ray diffraction, scanning electron microscopy, and energy dispersive spectroscopy. Mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…The positive effect on phase sizes reducing during alloying of Fe-B-C alloys with such elements as Cu, Ni and Mn is confirmed by Sukhova V.V. [44].…”
Section: Mechanical Propertiesmentioning
confidence: 70%
See 1 more Smart Citation
“…The positive effect on phase sizes reducing during alloying of Fe-B-C alloys with such elements as Cu, Ni and Mn is confirmed by Sukhova V.V. [44].…”
Section: Mechanical Propertiesmentioning
confidence: 70%
“…As known copper is hardly soluble in Fe2(В,С) and Fe(В,С) phases. It changes micro hardness and crack toughness coefficient of deposited metal very slightly [44].…”
Section: Researchmentioning
confidence: 99%
“…The amount of Cu in the matrix is increased [91] with the addition of Cu, as an anodes substance during corrosion, because the standard potential for the redox couple Cu 2+ /Cu is positive. Cu alloy elements are separated on the sample surface and formed a compact Cu-rich passive film [105] in the atomic scale.…”
Section: Discusionmentioning
confidence: 99%
“…Cu is a wellknown alloying element used to increase the overall corrosion resistance [86][87][88][89][90]. It is known the copper does not form compounds with boron (B) and remains mostly in the matrix [91], dissolving mostly in austenite [78]. Studies of alloys of the alloying system with a high boron content of 3.5% wt.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have attempted to improve the tribological properties of plain Fe-B alloys by adding alloying elements (Cr, Mn, Mo, Ti, etc. ); Cr is most often used [ 35 , 36 , 37 , 38 , 39 , 40 ]. Jian et al [ 35 , 36 ] found that adding 2 wt.% Cr increases the wear resistance of an Fe-3.0 wt.% B alloy under SiC and SiO 2 abrasion; if the Cr content is increased further, the wear resistance decreases.…”
Section: Introductionmentioning
confidence: 99%